Letter from Robert S. Mulliken to Harrison Shull, 1960 - Mulliken, Robert Sanderson (1960)
Letter between Robert S. Mulliken and Harrison Shull, American quantum chemists.
Keywords: Shull, Harrison; Mulliken, Robert Sanderson; Chemists; Parr, Robert G., 1921-; Nobel Prize winners; Physicists